tính hợp lí 11^2+13^2+15^2+...+201^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
trả lời:
B = 7x( 5/2x7 + 4/7x11 + 3/11x14 + 1/14x15 + 13/15x28 )
B = 7x(1/2 - 1/7 + 1/7 - 1/11 +....+ 1/15 - 1/28)
B = 7x(1/2 - 1/28)
B = 7x13/28
B = 13/4
Bàì làm:
\(B=\frac{5}{2.1}+\frac{4}{1.11}+\frac{3}{11.2}+\frac{1}{2.15}+\frac{13}{15.4}\)
\(B=7.\left(\frac{5}{2.7}+\frac{4}{7.11}+\frac{3}{11.14}+\frac{1}{14.15}+\frac{13}{15.28}\right)\)
\(B=7.\left(\frac{1}{2}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+\frac{1}{14}-\frac{1}{15}+\frac{1}{15}-\frac{1}{28}\right)\)
\(B=7.\left(\frac{1}{2}-\frac{1}{28}\right)\)
\(B=7.\frac{13}{28}\)
\(B=\frac{13}{4}\)
a) 2/9 - (1/20 + 2/9)
= 2/9 - 1/20 - 2/9
= (2/9 - 2/9) - 1/20
= 0 - 1/20
= -1/20
b) -3/14 + 2/13 + (-25/14) + (-15/13)
= (-3/14 - 25/14) + (2/13 - 15/13)
= -2 - 1
= -3
c) -3/11 + 11/8 - 3/8 + (-8/11)
= (-3/11 - 8/11) + (11/8 - 3/8)
= -1 + 1
= 0
d) 3/8 + (-1/4) - (7/12 - 1/6)
= 1/8 - 5/12
= -7/24
e) (1/3 + 12/67 + 13/41) - (79/67 - 28/41)
= 1/3 + 12/67 + 13/41 - 79/67 + 28/41
= 1/3 + (12/67 - 79/67) + (13/41 + 28/41)
= 1/3 - 1 + 1
= 1/3
`a)3/5+(-4/9)`
`=3/5-4/9`
`=27/45-20/45`
`=7/45`
`b)3/5+2/5 . 15/8`
`=3/5 + 30/40`
`=3/5+3/4`
`=12/20+15/20`
`=27/20`
`c)7/2 . 8/13 + 8/13 . (-5/2)`
`=8/13 . (7/2 +(-5)/2)`
`=8/13 . 1`
`=8/13`
`d)-5/17 . (-9/23)+9/23 . (-22/17) + 11 9/23`
`=-5/17 . (-9/23) + 9/23 . (-1) . 22/17 + 11 + 9/23`
`=-5/17 . (-9/23) + (-9/23) . 22/17+11+9/23`
`= -9/23 ( -5/17 + 22/17)+11+9/23`
`= - 9/23 . 1+11+9/23`
`=-9/23+11+9/23`
`=(-9/23+9/23)+11`
`=0+11`
`=11`
a: =27/45-20/45=7/45
b: =3/5+30/40
=3/5+3/4
=12/20+15/20
=27/20
c: =8/13(7/2-5/2+1)=8/13*2=16/13
d: =9/23*5/17-9/23*22/17+11+9/23
=-9/23+11+9/23
=11
Bài 2:
a: Ta có: \(\dfrac{9}{11}=1-\dfrac{2}{11}\)
\(\dfrac{13}{15}=1-\dfrac{2}{15}\)
mà \(-\dfrac{2}{11}< -\dfrac{2}{15}\)
nên \(\dfrac{9}{11}< \dfrac{13}{15}\)
b: Ta có: \(\dfrac{19}{15}=1+\dfrac{4}{15}\)
\(\dfrac{15}{11}=1+\dfrac{4}{11}\)
mà \(\dfrac{4}{15}< \dfrac{4}{11}\)
nên \(\dfrac{19}{15}< \dfrac{15}{11}\)
a,\(\frac{1}{5}\times\frac{2}{9}\div\frac{1}{15}\)
\(=\frac{1}{5}\times\frac{2}{9}\times15\)
\(=\left(\frac{1}{5}\times15\right)\times\frac{2}{9}\)
\(=3\times\frac{2}{9}\)
\(=\frac{2}{3}\)
b\(\frac{4}{15}\times\frac{7}{15}\times\frac{5}{4}\)
\(=\left(\frac{4}{15}\times\frac{5}{4}\right)\times\frac{7}{15}\)
\(=\frac{1}{3}\times\frac{7}{15}\)
\(=\frac{7}{45}\)
c,\(\frac{21}{23}\times\frac{5}{11}\times\frac{44}{?}\)
d,\(26\times\frac{13}{42}\div13\)
\(=\left(26\div13\right)\times\frac{13}{42}\)
\(=2\times\frac{13}{42}\)
\(=\frac{13}{21}\)
Lời giải:
$25\frac{2}{13}-(\frac{15}{17}+15\frac{2}{13)$
$=25+\frac{2}{13}-\frac{15}{17}-15-\frac{2}{13}$
$=(25-15)+(\frac{2}{13}-\frac{2}{13})-\frac{15}{17}$
$=10-\frac{15}{17}=\frac{155}{17}$
a) Ta có:
\(1-\frac{9}{11}=\frac{11-9}{11}=\frac{2}{11}\)
\(1-\frac{13}{15}=\frac{15-13}{15}=\frac{2}{15}\)
Vì \(\frac{2}{15}< \frac{2}{11}\Rightarrow1-\frac{9}{11}< 1-\frac{13}{15}\Rightarrow\frac{9}{11}>\frac{13}{15}\)
b) Ta có
\(\frac{201}{301}>\frac{201}{308}>\frac{199}{308}\Rightarrow\frac{201}{301}>\frac{199}{308}\)
=(3/2-9/10)+(5/6-17/42)+(7/12-13/4)+11/30-15/56
=3/5+37+(-29/12)+11/30-15/56
=29/30+39/56+29/12
=227/840
NHỚ K MÌNH NHA
mik đang cần gấp